Dancing Against falls iN Community-dwElling older adults (DANCE): a study protocol of a stratified, block-randomised trial. Issue 1 (20th September 2021) - Thomsen, Mikkel Jacobi; Liston, Matthew; Christensen, Merete Grothe; Vestergaard, Peter; Hirata, Rogerio Pessoto
Abstract : Background: Unintentional falls among older adults are of primary importance due to their impact on quality of life. Falling accounts for 95% of hip fractures, leading to an approximately six times increased risk of death within the first 3 months. Furthermore, physical and cognitive parameters are risk factors for falls. The purpose of this study is to examine the effect of a 6-month salsa dance training intervention, compared with regular fitness circuit training and a control group. Methods: This study will include 180 older adults: 90 healthy patients and 90 patients with osteoporosis. Participants will be allocated randomly in either of the groups, stratified according to age. Training groups will receive 2 weekly 1-hour training sessions, continuously through 6 months. Participants will be tested at baseline and 6 and 18 months post baseline. Primary outcome will be number of falls and secondary outcomes include bone mineral density, body composition, pain evaluation, weekly physical activity, single-task and dual-task gait patterns, balance, Fullerton Functional Fitness Test and assessment of the mini-BESTest. Discussion: This study will investigate the effects of a specially designed dance training programme (Dancing Against falls iN Community-dwElling older adults (DANCE)) to reduce the risk of falling among older adults. The study will investigate the effect against an active and passive comparator, resulting in the possibility to state, if DANCE training should be an alternative to traditional training. Trial registration number: NCT03683849 .